Impact of Self Control on Impulsive Buying, With Mediating Role of Impulsiveness of Social Networks and Moderating Role of Gender - Aysha Fayyaz; Dr. Mubashar Hassan Zia; Dr. Ali Haider (International Journal of Business and Economic Affairs, 2023)
This study investigates the influence of self-control on impulsive buying behaviour, emphasizing the mediating role of impulsiveness in social networks and the moderating role of gender. A quantitative research design was adopted, with data collected through an online survey from 350 young adults (aged 18-35) from provincial and federal capitals of Pakistan. Respondents were contacted via social media platforms, and measures for self-control, impulsiveness of social networks, and impulsive buying were adapted from established scales. Data was analysed using Structural Equation Modelling (SEM) and Process by Hayes for testing mediation and moderation effects. The results indicate that low self-control has a significant positive impact on impulsive buying. Impulsiveness of social networks also significantly affects impulsive buying and mediates the relationship between low self-control and impulsive buying. Furthermore, gender moderates this relationship, with females exhibiting a stronger tendency toward impulsive buying under conditions of low self-control compared to males. The study highlights the need for marketers to consider the role of social networks and gender when targeting consumers prone to impulsive buying. Gender-specific marketing strategies, particularly in online environments, can be effective in managing impulsive buying tendencies. This research extends the understanding of how individual factors like self-control and social influences interact with demographic variables such as gender in shaping impulsive buying behaviour. It fills gaps identified in previous literature by examining these relationships within an emerging market context.